2019
DOI: 10.1007/s13167-019-00178-x
|View full text |Cite
|
Sign up to set email alerts
|

Association among resistin, adenylate cyclase-associated protein 1 and high-density lipoprotein cholesterol in patients with colorectal cancer: a multi-marker approach, as a hallmark of innovative predictive, preventive, and personalized medicine

Abstract: Background Elevated concentrations of resistin have been reported in colorectal cancer (CRC), but its interactions with adenylate cyclase-associated protein 1 (CAP-1) are largely unexplored. We investigated resistin plasma concentration, peripheral blood mononuclear cells (PBMCs) resistin messenger ribonucleic acid (mRNA), and CAP-1 mRNA levels in CRC patients, as well as the impact of resistin gene polymorphism rs1862513 on the examined markers. We also explored associations of resistin with high-density lipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…Resistin was reportedly increased in subjects with rectal cancer and in correlation with insulin levels in CRC patients [76]. Similarly, our study demonstrated increased levels of resistin and its receptor adenylate cyclase-associated protein 1 in CRC [77]. Also, a meta-analysis pointed towards elevated resistin levels in CRC patients [78].…”
Section: Insulin Resistancesupporting
confidence: 81%
See 1 more Smart Citation
“…Resistin was reportedly increased in subjects with rectal cancer and in correlation with insulin levels in CRC patients [76]. Similarly, our study demonstrated increased levels of resistin and its receptor adenylate cyclase-associated protein 1 in CRC [77]. Also, a meta-analysis pointed towards elevated resistin levels in CRC patients [78].…”
Section: Insulin Resistancesupporting
confidence: 81%
“…Therefore, the predominance of small, dense LDL represents a critical factor for the development and progression of atherosclerosis [182] and endothelial dysfunction, which both amplify the risk of cardiovascular events [181]. Some inflammatory cytokines, such as resistin, are closely associated with these LDL subspecies and seem to play a role in both diabetes and colon cancer development [77,183].…”
Section: Novel Antidiabetic Glucagon-like Peptide-1 Receptor Agonists (Glp-1ras) Therapies and Colorectal Cancermentioning
confidence: 99%
“…An increase in Resistin plasma levels and CAP1 expression in peripheral blood mononuclear cells has been reported in colorectal cancer patients (Mihajlovic et al, 2019). Resistin can also contribute to pancreatic cancer pathogenesis, since its levels are increased in pancreatic cancer patients and correlate positively with tumor grades.…”
Section: Cap1 At the Crossroads Of Metabolism And Cancermentioning
confidence: 96%
“…Further, its higher expression is found associated with poor prognosis, nodal metastasis, and advanced cancer stage in colorectal cancer patients [ 126 ]. It is important to state that its expression was negatively associated with high density lipoprotein cholesterol (HDL-C) in colorectal cancer patients because of a possible interaction of its release with HDL-C [ 127 ].…”
Section: Introductionmentioning
confidence: 99%